2016
DOI: 10.1186/s12884-016-0912-1
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and preferences of care among Swedish immigrants following a prenatal diagnosis of congenital heart defect in the fetus: a qualitative interview study

Abstract: BackgroundImmigrants experience significant challenges when in contact with healthcare and report less satisfaction with maternity care compared to native Swedes. Research that gives voice to pregnant immigrant women and their partners following a prenatal diagnosis of a fetal anomaly is scarce. Thus, the aim of this study was to explore experiences and preferences of care following a prenatal diagnosis of congenital heart defect among Swedish immigrants.MethodsPregnant immigrants and their partners were conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 35 publications
1
38
0
1
Order By: Relevance
“…The studies that stated their participants" precise ethnicity or country of birth reported them originating from 29 different countries. Of these countries, the largest representation was in Somalia (Garnweidner et al 2013;Degni et al 2014;Lillrank 2015;Byrskog et al 2016;Carlsson et al 2016;Glavin & Saeteren 2016;Barkensjö et al 2018;Hjelm et al 2018), Afghanistan (Garndweidner et al 2013;Lillrank 2015;Barkensjö et al 2018), and Morocco (Robertson 2015;Barkensjö et al 2018;Hjelm et al 2018). The distribution of all of the study participants" reported countries of origin shared as to follow in Table 4.…”
Section: Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies that stated their participants" precise ethnicity or country of birth reported them originating from 29 different countries. Of these countries, the largest representation was in Somalia (Garnweidner et al 2013;Degni et al 2014;Lillrank 2015;Byrskog et al 2016;Carlsson et al 2016;Glavin & Saeteren 2016;Barkensjö et al 2018;Hjelm et al 2018), Afghanistan (Garndweidner et al 2013;Lillrank 2015;Barkensjö et al 2018), and Morocco (Robertson 2015;Barkensjö et al 2018;Hjelm et al 2018). The distribution of all of the study participants" reported countries of origin shared as to follow in Table 4.…”
Section: Populationmentioning
confidence: 99%
“…Five studies were conducted in Sweden (Robertson 2015;Byrskog et al 2016;Carlsson et al 2016;Barkensjö et al 2018;Hjelm et al 2018), three in Norway (Garnweidner et al 2013;;Viken et al 2015;Glavin &Saeteren 2016), andtwo in Finland (Degni et al 2014;Lillrank 2015). Other Nordic countries were not represented in the articles that met all of the inclusion criteria.…”
Section: Contextmentioning
confidence: 99%
“…Algumas malformações nem sempre são aparentes no Recém-Nascido (RN), podendo levar dias, meses ou até anos para se manifestarem (Ni et al, 2019). De etiologia variada, as CCs podem ser desencadeadas por diversos fatores, como: genético, hereditário, ambiental e social (Carlsson, Marttala, Mattsson & Ringnér, 2016a;Carlsson, Bergman, Wadensten & Mattson, 2016b;Queirora et al, 2017;Im et al, 2018).…”
Section: Assistência Multiprofissional E Interdisciplinar Na Abordagem Das Cardiopatias Congênitasunclassified
“…Despite this, migrant mothers continue to face di culties for successful BF [11][12][13][14][15][16][17][18][19][20][21] . This is why some researchers suggest that culturally adapted health services are necessary to maintain BF rates in migrant mothers 10,22 .…”
Section: Introductionmentioning
confidence: 99%